Youth-adult relationships within community-based programs: their impact on the development of youth empowerment - Hardman, Alisha M. (Kansas State University, 2008)
The current study focuses on qualitative data collected from youth and adults in two rural Kansas communities. The focal point of analysis was youth and adults' answers to questions about their experiences working with one another within community-based programs, specifically questions regarding youth's feeling of empowerment within the context of the program. Lerner's theory of developmental contextualism provided a framework for understanding how youth-adult relationships contribute to the development of youth empowerment. Youth voice, a construct related to the youth empowerment literature, appeared in the participants' responses across program sites. Common themes across settings were that teens who had been involved in the program the longest felt especially empowered, that youth became more responsible as a result of participating in the program, and that adults in both program sites fulfilled the six adult roles for youth empowerment that have been established in the research literature. Finally, three constructs significant in the youth development literature (confidence, connection and compassion) emerged as themes in relation to the experiences of the young people in the program. Implications of this study include exploring the impact youth-adult relationships have on adults and investigating how teens as role models or mentors for "littles" impact their feeling of empowerment. Suggestions for replication of this study are also given.
Keywords: Positive youth development; Youth-adult partnerships; Youth empowerment; Community-based youth programs; Adolescence; Health Sciences, Human Development (0758)